Fox Insight collects online, longitudinal patient-reported outcomes and genetic data on Parkinson’s disease - Luba Smolensky (Nature Portfolio, 2020)
Measurement(s) Parkinson’s disease • Patient Reported Outcome • SNP Technology Type(s) questionnaire • crowd sourced data generation • single-nucleotide polymorphism analysis Factor Type(s) cohort • data acquisition source • temporal interval • environmental risk factor • mds updrs • geriatric depression scale • medical history • family neurological history • sleep disorder • handedness • demographics • physical activities • caregiver • daily living • LRRK2 • APOE • SNCA • GBA Sample Characteristic - Organism Homo sapiens Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.11794011